Hubungan Tingkat Pengetahuan Ibu Hamil Dengan Tanda Bahaya Kehamilan Trimester III Di Wilayah Kerja Puskesmas Bluto Kecamatan Bluto Kabupaten Sumenep - Ratna Indriyani; Sri Sumarni; Sri Yunita Suraida Salat (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2018)
Complication of pregnancy is one the causes of the high maternal mortality rate (MMR) in indonesia to date, which is bleeding as much as 28% and the poisoning of pregnancy (eclampsia) as much as 24%. The purpose of this study is to analyze the relationship of the knowledge level of pregnant women with danger sign of third trimester pregnancy. This research design is a quantitative research using design of analytic research design with cross sectional method with population of 42 pregnant women where the sample was taken 33 pregnant women sampling technique that is simple random sampling data analysis using chi square The results of research that the age of most pregnant women aged 24-26 that as many as 9 (27,3%) pregnant women. The level of education of pregnant women has a background of education as many as 14 (42,4%). SMP work of pregnant women working as housewives as many as 19 (57,6%) pregnant women. The level of knowledge of pregnant women as much as 23 (69,7%) have less knowledge. pregnant women have a danger sign of third trimester pregnancy. From P-value research result from chi square correlation test statistics of 0,000 and bacause P < α,(0,000<0,05) then the decision taken is H0 rejected, H1 accepted that there is a relationship of knowledge level of pregnant women with danger sign of third trimester pregnancy the working area of puskesmas bluto bluto district of sumenep regency. Based on the above conclusions it is suggested to health workers to improve the quality, frequency of the counseling to pregnant women about the sign of third trimester Pregnancy The Working Area Of Puskesmas Bluto Bluto District Of Sumenep Regency.